2002
DOI: 10.1161/01.hyp.0000024348.87637.6f
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin Prevents Angiotensin II–Induced Cardiac Alteration and Oxidative Stress

Abstract: Abstract-The influence of the HMG-CoA reductase inhibitor simvastatin was assessed on the cardiovascular alterations and production of free radicals associated with chronic angiotensin II (Ang II) infusion. Simvastatin (60 mg/kg per day PO) or placebo were given concomitantly for 10 days in Sprague-Dawley rats infused with Ang II (200 ng/kg per minute SC, osmotic pump). In addition, simvastatin or placebo was also given in vehicle-infused rats. Tail-cuff pressure and albuminuria were measured before and at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
90
2
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 141 publications
(100 citation statements)
references
References 69 publications
5
90
2
3
Order By: Relevance
“…Second, simvastatin prevents cardiac hypertrophy in rats receiving angiotensin II infusion. 44 Statins downregulate AT1R expression in platelets and vascular smooth muscle cells. 45,46 Thus, simvastatin may prevent SAD-induced aggravation of hypertensive cardiac hypertrophy, at least in part, by inhibiting the angiotensin II-mediated mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Second, simvastatin prevents cardiac hypertrophy in rats receiving angiotensin II infusion. 44 Statins downregulate AT1R expression in platelets and vascular smooth muscle cells. 45,46 Thus, simvastatin may prevent SAD-induced aggravation of hypertensive cardiac hypertrophy, at least in part, by inhibiting the angiotensin II-mediated mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Therefore, the ability of statins to inhibit ICAM-1 expression indicates that statins can attenuate leukocyte-endothelial cell interactions and the subsequent endothelial damage and tissue injury. Indeed, many studies have reported that statins can inhibit leukocyte-endothelial cell interactions in many conditions, such as thrombin-activated leukocyte-endothelial cell interactions, 47 angiotensin II-induced injury, 35,48 transient ischemic injury, 36,49 and Staphylococcus aureus ␣-toxin-induced inflammation. 14 These results provide the best evidence to support the view that statins can inhibit leukocyte-endothelial cell interactions independent of their lipid-lowering effect.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35][36][47][48][49] These differences may derive from the diversity of the mechanisms of each model or duration of the drug administration. In addition, many studies with streptozotocin-induced diabetic animals were performed for a relatively short duration compared to chronic diabetes in human.…”
Section: Discussionmentioning
confidence: 99%
“…Values of four clearance measurements were averaged to provide a single value for glomerular filtration rate (GFR) and effective renal plasma flow. Urinary excretion of albumin was determined by immuno-nephelemetric method (3).…”
Section: Methodsmentioning
confidence: 99%